Application of music-guided imagination on relief of anxiety in a patient undergoing High ligation and stripping of the greater saphenous vein (音乐引导性想象技术改善1例大隐静脉高位结扎加分段剥脱手术患者焦虑状态的护理) - ZHANG Shaojuan (张少娟); HUANG Yanping (黄砚萍) (Journal of International Translational Medicine Limited, 2022)
This paper observe the effect of music-guided imagination on relief of anxiety in a patient undergoing high ligation and stripping of the greater saphenous vein. Keys issues of preoperative preparation, intraoperative cooperation, music-guided imagination and postoperative observation were summarized. The music-guided imagination is potentially effective to relieve the patient's anxiety and improve the surgical compliance. (本文总结了运用音乐引导性想象疗法改善1例行大隐静脉高位结扎加分段剥脱手术患者焦虑状态的效果及护理经验, 包括术前准备、术中配合、音乐引导性想象疗法操作方法、术后观察等。音乐引导性想象疗法能够有效缓解患者围手术期焦虑情绪, 提高手术配合度, 对减少并发症、加快术后康复有着积极作用。)